2001
DOI: 10.1002/j.2333-8504.2001.tb01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of Lpi Ratings for Native‐korean Speakers in the Toeic Testing Context: Search for Explanation

Abstract: Regression‐based guidelines have been developed for predicting ratings of speaking proficiency in English as a foreign language (EFL), as assessed using the Language Proficiency Interview (LPI) procedure, from scores on the TOEIC® (Test of English for International Communication) Test. These guidelines, which reflect the regression of LPI rating on TOEIC scores in a combined sample composed of native speakers of Japanese, French, Spanish, and Arabic, respectively, were found to overestimate LPI rating when app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The remarkable success by Korean‐American students might be of special interest in view of the salient linguistic distance between English and Korean language systems. For instance, Wilson (2001) noted that English as a foreign language (EFL) speaking proficiency tends to lag behind the proficiencies that are assessed by the TOEIC test relatively more in native‐Korean‐speaking EFL learners than in demographically comparable EFL learners in other national/linguistic settings. Specifically, in Wilson's study, the regression of the interview ratings on TOEIC scores in a combined sample composed of native speakers of Japanese, French, Spanish, and Arabic, respectively, was found to overestimate the interview rating when applied to data for native speakers of Korean.…”
Section: Resultsmentioning
confidence: 99%
“…The remarkable success by Korean‐American students might be of special interest in view of the salient linguistic distance between English and Korean language systems. For instance, Wilson (2001) noted that English as a foreign language (EFL) speaking proficiency tends to lag behind the proficiencies that are assessed by the TOEIC test relatively more in native‐Korean‐speaking EFL learners than in demographically comparable EFL learners in other national/linguistic settings. Specifically, in Wilson's study, the regression of the interview ratings on TOEIC scores in a combined sample composed of native speakers of Japanese, French, Spanish, and Arabic, respectively, was found to overestimate the interview rating when applied to data for native speakers of Korean.…”
Section: Resultsmentioning
confidence: 99%
“…Boldt & Ross, 1998, n.d.), and relationships with other measurement scales (e.g. Powers et al, 2008;Tannenbaum & Wylie, 2005;Wilson, 1999Wilson, , 2001. For example, Woodford (1982), in what was perhaps the first validation study of the TOEIC test, reported high reliability indices of .916, .930, and .956 for the listening, reading, and whole sections.…”
Section: Validation Studies On the Toeic Testmentioning
confidence: 99%
“…Princeton University Educational Testing Service reported that the test-retest reliability of TOEIC was 0.96, based on its administration to 2,710 test-takers in Japan in 1979 (Chapman, 2006). TOEIC scores correlated r = 0.83 with other measures of ESL (English as a second language) proficiency (Wilson, 2001).…”
Section: Methodsmentioning
confidence: 81%